2016
DOI: 10.1021/acsami.6b00386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphorus-Doping on Electrochemical Performance of Silicon Negative Electrodes in Lithium-Ion Batteries

Abstract: The effect of phosphorus (P)-doping on the electrochemical performance of Si negative electrodes in lithium-ion batteries was investigated. Field-emission scanning electron microscopy was used to observe changes in surface morphology. Surface crystallinity and the phase transition of Si negative electrodes before and after a charge-discharge cycle were investigated by Raman spectroscopy and X-ray diffraction. Li insertion energy into Si was also calculated based on computational chemistry. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
116
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(126 citation statements)
references
References 45 publications
9
116
1
Order By: Relevance
“…The Si layer in the PC became porous after the 20th cycle, whereas that in the PP1MEM‐FSA was not very porous. A similar phenomenon has been reported for other Si‐based electrodes in PC . Therefore, this phenomenon can be attributed to the electrolyte rather than the electrode.…”
Section: Resultssupporting
confidence: 83%
“…The Si layer in the PC became porous after the 20th cycle, whereas that in the PP1MEM‐FSA was not very porous. A similar phenomenon has been reported for other Si‐based electrodes in PC . Therefore, this phenomenon can be attributed to the electrolyte rather than the electrode.…”
Section: Resultssupporting
confidence: 83%
“…6a, while the lithiation process of carbonized gelatin also makes a bit of contribution, which can be confirmed by Fig. 6b and d. In the anodic sweep, two peaks at around 0.3 V and 0.5 V are assigned to the extraction of Li-ions from Li-Si alloys [44,45] and amorphous Si is formed [46]. In the following lithiation process, the amorphous Si, instead of the initial crystalline Si, takes part in the lithiation reaction.…”
Section: Resultssupporting
confidence: 57%
“…Each silicide electrode was prepared by a gas deposition (GD) method, which does not require a binder or conductive agent . The detailed conditions of GD were described in our previous paper . The weight of the deposited active material was 30±2 μg.…”
Section: Methodsmentioning
confidence: 99%
“…Many research groups have put significant efforts into these issues: coating Si with conductive materials to reduce the electrical resistivity, synthesizing nanostructured Si materials to cushion volume expansion,, doping Si with impurities to increase its electrical conductivity and/or suppress its phase transition from Si to crystalline Li 15 Si 4 phases ,. We have previously reported that a composite electrode that consisted of elemental Si and a binary silicide (M y Si z , M : metal), such as LaSi 2 and Gd−Si, shows a superior electrochemical performance in conventional organic electrolytes compared to the Si‐alone electrode ,.…”
Section: Introductionmentioning
confidence: 99%